Conflict in Darfur in the perspective of genocide prevention - Kościółek, Jakub (The Opole Studies in Administration and Law, 2019)
The article presents the records collected by the Darfur Atrocities Documentation Team (ADT), which have proved the occurrence of genocide in Darfur. It describes the discussion of the academic community and often conflicting political positions on the issue. The author attempted to analyse the results of the work of the International Commission of Inquiry on Darfur (ICID), appointed at the request of the United States by the UN Security Council, which examined the numerous violations of the international law in the province, but did not express an opinion whether or not genocide had taken place in Darfur. He has confronted the collected evidence of crimes committed in Darfur with the “Convention on the prevention and punishment of genocide”, which obliges the international community to intervene when genocide is proved to be happening. The conflict in Darfur has been presented as an example of the ineffectiveness of the response of the international community to genocide. Therefore, an analysis was carried out on the means of effective prevention of genocide, which can be used in future prevention of crimes in other regions of the world.